Poor oral function is associated with loss of independence or death in functionally independent older adults. - Yusuke Nagamine (Public Library of Science (PLoS), 2021)
Aim To clarify the association of poor oral function with loss of independence (LOI) or death in functionally independent older adults in the community. Methods We conducted a secondary analysis of data from a prospective cohort study in two municipalities in Japan. We included participants who were older than 65 years of age and had no certification in long-term care at baseline. Poor oral function was evaluated by the Kihon Checklist. Among participants with poor oral function, they were further classified by the degree of quality of life (QOL) impairment due to dysphagia. Main outcome is LOI or death from all cause. The hazard ratio (HR) and 95% confidence of intervals (CIs) were estimated by Cox proportional hazard models adjusted for potential confounders. Results Of 1,272 participants, 150 participants (11.8%) had poor oral function. The overall incidence of LOI or death was 10.0% in the participants with poor oral function, while 3.3% in the participants without. Participants with poor oral function were more likely to develop LOI or death than those without (crude HR = 3.17 [95% CIs 1.74-5.78], adjusted HR = 2.30 [95% CIs 1.22-4.36]). 10 participants (0.79%) were classified as poor oral function with QOL impairment, and were more likely to develop LOI or death than those without poor oral function (crude HR = 7.45 [95% CIs 1.80-30.91], adjusted HR = 8.49 [95% CIs 1.88-38.34]). Conclusions Poor oral function was associated with higher risk of LOI or death in functionally independent older adults in the community.